Experimental Analysis on Hybrid Polymer Gears Produced with Fused Deposition Modeling Method: Thermal Behavior and Wear - Igor Šuljić; Vjekoslav Tvrdić; Milan Perkušić; Ivan Vrljičak (Applied Sciences)
In this study, an experimental analysis of the thermal behavior and wear of polymer and hybrid polymer gears produced with the Fused Deposition Modeling (FDM) method was performed. Compared to conventional polymer gear manufacturing methods, the FDM process represents an energy-efficient material forming method. The low thermal conductivity of polymer gears has an impact on heating, which limits their application. The novelty of this research is an experimental analysis on hybrid polymer gears, and, for this purpose, a new hybrid polymer gear design with aluminum and steel inserts has been proposed. An in-house-developed non-mechanically closed-loop test rig was used to investigate Polyamide (PA) gears under different loads. An accelerated step load test procedure was employed, while the gears’ bulk temperature was recorded with a thermal imaging camera. The print quality affected the tooth flank surface roughness, so polymer gears with two different print qualities were initially produced. Hybrid polymer gears were produced with a higher print quality, since the print quality had an influence on the heating and wear. The correlation between the bulk temperature and wear was observed for all of the tested gears. A novel design of hybrid polymer gears with aluminum inserts achieved up to a 9 °C (17%) lower bulk temperature and a higher wear resistance.